The Future of Cryopreservation in Assisted Reproductive Technologies - Bosch, Ernesto; De Vos, Michel; Humaidan, Peter (Frontiers in Endocrinology, 2020)
Societal changes and the increasing desire and opportunity to preserve fertility have increased the demand for effective assisted reproductive technologies (ART) and have increased the range of scenarios in which ART is now used. In recent years, the ‘freeze-all’ strategy of cryopreserving all oocytes or good quality embryos produced in an IVF cycle to transfer later—at a time that is more appropriate for reasons of medical need, efficacy or desirability—has emerged as an accepted and valuable alternative to fresh embryo transfer. Indeed, improvements in cryopreservation techniques (vitrification) and the development of more efficient ovarian stimulation protocols have facilitated a dramatic increase in the practice of elective frozen embryo transfer (eFET). Alongside these advances, debate continues about whether eFET should be a standard treatment option available to the whole IVF population or if it is important to identify patient subgroups who are most likely to benefit from such an approach. Achieving successful outcomes in ART, whether by fresh or frozen embryo transfer, is influenced by a wide range of factors. As well as the efficiency of IVF and embryo transfer protocols and techniques, factors affecting implantation include maternal aging, sperm quality, the vaginal and endometrial microbiome, and peri-implantation levels of serum progesterone. The safety of eFET, both during ART cycles and on longer-term obstetric and neonatal outcomes, is also an important consideration. In this review, we explore the benefits and risks of freeze-all strategies in different scenarios. We review available evidence on the outcomes achieved with elective cryopreservation strategies and practices and how these compare with more traditional IVF cycles with fresh embryo transfers, both in the general IVF population and in subgroups of special interest. In addition, we consider how to optimize and individualize ‘freeze-all’ procedures to achieve successful reproductive outcomes.